Nature and human emotions - Rolston, Holmes, 1932-2025, author; The Applied Philosophy Program, publisher (Colorado State University. Libraries, 1979)
Our encounter with nature is as passionate as it is cognitive. We have emotions of discontinuity before a nature we resist and fear. Our centripetal self maintains its integrity against the centrifugal wildness. There are also emotions of continuity, a nature we embrace and love--our country, the hills and rivers of home. Human emotions defend the self, aloft and transcendent over nature, but they ought also fit us to the surrounding natural environment. These are emotions that we all live by; they are emotions that some of us live for.
Keywords: social environment; nature; passion; emotions; cognitive processes; emotional processes